Simulation and Experimental Study of a 2D Photonic Crystal Structure that Reflects a Quantum Dots Emission in the Normal Direction - Isnaeni,; Cho, Yong Hoon (UI Scholars Hub, 2016)
Two-dimensional photonic crystal structures not only confine light and guide waves laterally but also reflect light in the normal direction due to a slow Bloch mode effect. However, evidence of the utilization of this structure as a mirror is required. Therefore, in this work, a simulation was made and experimental results were obtained to prove that there was an increase in the intensity of reflected CdSe colloidal quantum dots emission in the normal direction when a 2D photonic crystal structure was used. A thin TiO2 film was shaped into a two-dimensional photonic crystal structure using a simple sol-gel and polystyrene-mask-etching procedure. This structure was then placed on top of the thin CdSe quantum dots film layer. The emission of quantum dots onto the two-dimensional photonic crystal structure was compared to quantum dots emission onto a flat, thin TiO2 film. An increase in the quantum dots emission of up to 105% was in the presence of the two-dimensional photonic crystal structure. This finding is very useful for photonic device applications, such as light-emitting diodes, laser systems and bio-tagging detection systems.